Efficacy of a specific polyclonal equine F(ab')2 against avian influenza (H5N1) in ferrets: synergy with oseltamivir. (September 2016) - Herbreteau, Cécile H; Denizot, Mélanie; Lowther, Suzanne; Riddell, Sarah; Frazer, Leah; Haining, Jessica; Arkinstall, Rachel; Payne, Jean; Harper, Jenni; Johnson, Dayna; Pasquier, Anaïs; Middleton, Deborah; et al.
Aim: Current therapies against avian influenza (H5N1) provide limited clinical benefit. FBF-001 is a highly purified equine polyclonal immunoglobulin fragment against H5N1.Methods: Using a ferret model of severe acute H5N1 infection, we assessed FBF-001 when administered on the same day or 1 day after viral challenge, in comparison with oseltamivir therapy.Results: Untreated animals died 2–3 days after challenge. FBF-001 prevented most severe illness and reduced nasal viral load, with best efficacy when administered on the day of viral challenge. Oseltamivir and FBF-001 had synergistic impact on survival.Conclusion: FBF-001 prevented severe consequences of lethal H5N1 challenge in ferrets by controlling viral replication, an effect synergistic to oseltamivir. FBF-001 has recently been granted EMA orphan drug status.